A Universal Strategy of Intermolecular Exchange to Stabilize α‐FAPbI3 and Manage Crystal Orientation for High‐Performance Humid‐Air‐Processed Perovskite Solar Cells. Issue 23 (2nd May 2022) - Wang, Min; Sun, Haoxuan; Meng, Linxing; Wang, Meng; Li, Liang
Abstract: Preparation of high‐performance perovskite solar cells without strict environmental control is an inevitable trend of commercialization. Humidity is considered the main factor hindering perovskite performance. Formamidine (FA)‐based perovskites suffer from the instability of photoactive black α‐FAPbI3, especially in humid air, and numerous defects in the surface and bulk of perovskite films limit their performance. In this work, long‐chain n‐heptylamine (nHA) is introduced via antisolvent engineering into an FA‐based perovskite film. nHA removes the negative intermediate adduct and promotes the formation of α‐FAPbI3 at room temperature in humid air via intermolecular exchange behavior. Moreover, the existence of nHA in the final perovskite film also reduces the defects and suppresses ion migration. The champion device delivers a power conversion efficiency (PCE) of 23.7% (certificated 22.76%) with negligible hysteresis, and the fabricated devices exhibit superior reproductivity. The device stability is also enhanced, maintaining 95% of its initial PCE after 1500 h in ambient air. Moreover, the PCE has no attenuation at the maximum power point under continuous 1‐sun light soaking for 500 h. The universality of this method is also demonstrated by other perovskite compositions, including methylamine lead iodine (MAPbI3 ) and FA x MA1− x PbI3 in humid air. Abstract : Long‐chain n‐heptylamine is introduced via antisolvent engineering into a formamidine (FA)‐based perovskite film, which promotes the formation of α‐FAPbI3 at room temperature in humid air via intermolecular exchange behavior. The champion device delivers a power conversion efficiency of 23.7% (certificated 22.76%) with negligible hysteresis and superior stability.